Simulation of the Impact of Instantaneous Solar UV Radiation Enhancements on the Middle Atmosphere via UV Radiation Reconstruction - Dan Liu; Junfeng Yang; Xiong Hu; Xuan Cheng; Cunying Xiao (Atmosphere, 2022)
This study reconstructed the 0.01–399.5 nm ultraviolet (UV) radiation band with a time resolution of 5 min under solar minimum conditions (18 October 2006) to investigate the effects of the solar flare event on the middle atmosphere. Five-minute resolution 0.01–399.5 nm UV radiation was used instead of daytime scale data to observe the response of the middle atmosphere to the instantaneous solar UV radiation enhancement. The results indicate that small temperature increases of 0.05 K in low latitudes were observed in the lower thermosphere and the stratosphere. The UV radiation enhancement led to an ozone increase of 0.6% in the stratosphere, which caused small temperature increases; and there is an ozone increase of up to 4% at 80 km, while a change of −2% occurred at 60–70 km and a change of −6% occurred in the low thermosphere. There was a 0.05% increase in atmospheric density above 60 km, and there was an increase of up to 0.15% at 80–90 km. The responses of the atmospheric temperature and density in the middle atmosphere to instantaneous UV radiation enhancements can therefore be captured via the UV radiation reconstruction. The simulation results were weaker than the previous study.